Effects of isometric strength and plyometric training on running performance: a randomized controlled study - Lum, Danny (2022)
The aim of the study was to compare the effects of isometric strength (IST) and plyometric training (PT) on endurance running performance. Methods: Twenty-six endurance runners (18 males and 8 females; age 36 +/- 6 years, stature 1.69 +/- 0.05 m body mass 61.6 +/- 8.0 kg, VO2max 50.4 +/- 5.8 ml center dot kg(-1)center dot min(-1)) completed the countermovement jump (CMJ), isometric mid-thigh pull (IMTP), 2.4 km run time trial (2.4kmTT), running economy test (RE) and a graded exercise test measures at baseline. They were then randomly assigned to three groups, the control (CON), PT or IST group, and completed the circuit, plyometric or isometric training, respectively, twice a week for 6 weeks, while still continuing to perform their planned running training. They then completed the same set of measures performed at baseline post-intervention. Results: Significant time x group interactions and time main effect were observed for 2.4kmTT (P = .002, n(p)(2) = .45 and P < .001, n( )(2)=0.72), maximal aerobic speed (MAS) (P = .006, n(p)(2) = .39), CMJ height (P < .001, n(p)(2) = .55) and IMTP relative peak force (P = .001, n(p)(2) = .50) in favor of PT and IST. Significant main effect for time was observed for 2.4kmTT (P < .001, n(p)(2) = .72), RE (P = .048, n(p)(2) = .17), VO2max (P = .047, n(p)(2) = .18), MAS (P < .001, n(p)(2) = .63), CMJ height (P < .001, n(p)(2) = .51) and IMTP relative peak force (P < .001, n(p)(2) = .58). Conclusion: In conclusion, both PT and IST were similarly effective at enhancing running endurance performance. However, IST resulted in greater improvement to RE.